2001
DOI: 10.1353/mpq.2001.0018
|View full text |Cite
|
Sign up to set email alerts
|

Peer and Teacher Sociometrics for Preschool Children: Cross-Informant Concordance, Temporal Stability, and Reliability

Abstract: Cross-informant concordance (peers vs. teachers), temporal stability, and reliability associated with sociometrics were systematically examined in a sample of 84 preschoolers (M ϭ 4.5 years). Structural equation modeling analyses revealed that parallel forms of teacher and peer sociometrics measured overlapping and unique aspects of peer popularity. Reliability, a characteristic of a measurement instrument (sociometric assessment), was differentiated from stability, which is associated with the phenomenon or b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
70
0
3

Year Published

2004
2004
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(79 citation statements)
references
References 51 publications
6
70
0
3
Order By: Relevance
“…Given that both peers and teachers share some common environments in which they observe a target child's behavior (e.g., classroom, lunchroom), they might show some agreement in their perceptions of the child's behaviors. In fact, research has shown moderate consensus between peers and teachers in their evaluations of children's social status (Landau, Milich, & Whitten, 1984;Wu, Hart, Draper, & Olsen, 2001) and academic skills (Gest, Domitrovich, & Welsh, 2005). However, different perceptions between teachers and peers might also be important to consider given their distinct social experiences with children.…”
Section: Peers and Teachers As Judges Of Children's Social Skillsmentioning
confidence: 99%
“…Given that both peers and teachers share some common environments in which they observe a target child's behavior (e.g., classroom, lunchroom), they might show some agreement in their perceptions of the child's behaviors. In fact, research has shown moderate consensus between peers and teachers in their evaluations of children's social status (Landau, Milich, & Whitten, 1984;Wu, Hart, Draper, & Olsen, 2001) and academic skills (Gest, Domitrovich, & Welsh, 2005). However, different perceptions between teachers and peers might also be important to consider given their distinct social experiences with children.…”
Section: Peers and Teachers As Judges Of Children's Social Skillsmentioning
confidence: 99%
“…In their study of children of preschool age, Wu et al (2001) did distinguish between stability and reliability. However, they confined themselves to establishing the reliability of variables indicating the concept popularity, but did not report correlations between two consecutive sociometric classifications.…”
Section: Stability and Reliability Of Sociometric Methodsmentioning
confidence: 99%
“…The composition of subgroups of the total research sample could have been rearranged (for example, class groups within a school). But social preferences may also easily change within fixed subgroups, particularly when young children are involved (Wu, Hart, Draper, & Olsen, 2001).…”
Section: Stability and Reliability Of Sociometric Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…RESUMO O conceito de sociometria, introduzido por Moreno (1934Moreno ( /1953, refere-se a um conjunto de métodos que permitem identificar, simultaneamente, a estrutura social dos grupos e a posição relativa que cada indivíduo ocupa, na referida estrutura. Não obstante a sua utilização recorrente, em diversos campos da psicologia, são poucos os estudos (e.g., Jiang & Cillessen, 2005;Wasik, 1987;Wu, Hart, Draper, & Olsen, 2001) que, durante o período correspondente ao pré-escolar (i.e., entre os 3 e os 5 anos de idade), avaliam a questões da concordância entre as avaliações obtidas através de diferentes medidas, sendo mais comum que se considere a estabilidade de cada medida, de modo a analisar, por exemplo, a evolução das classificações sociométricas (i.e., estatuto no grupo de pares). No presente estudo, foram entrevistados 263 crianças, 140 do sexo feminino e 123 do sexo masculino, distribuídas por 11 grupos (3 de 3 anos, 4 de 4 anos e 4 de 5 anos de idade), utilizando três técnicas sociométricas diferentes: (1) nomeações -3 escolhas positivas, 3 negativas (2) escala de apreciação (rating scale) -cada criança foi classificada entre 1 (não gosta muito de brincar) e 3 (gosta muito de brincar); e (3) comparação entre pares (paired comparisons) -escolha de uma entre duas crianças, pelo critério gosta mais de brincar, em todas as díades possíveis no grupo.…”
Section: Correlação Entre As Medidas Sociométricas Em Função Da Idadeunclassified